Dydaktyzm jako forma wypowiedzi poetyckiej w „Sztuce kochania” Owidiusza - Zagórski, Mariusz (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza, 2009)
The author presents and analyses certain epideictic aspects of Ovid’s Art of Love, concentrating in his discussion especially on the self-ironic passages.

Didactic elegy takes an important place in Ovid’s poetry and situates itself in the Roman literary tradition of the genre. While the poem of Lucretius is a substantially philosophical didactic and Vergil’s Georgica, although it is not above all a manual of agriculture, propagates an Augustan ideology, the didactic of Ovid's Ars amatoria seems to be a splendid emanation of poetical wit rather than an attempt at teaching its readers. It results, that it is the world reverted, where the pure charm of form dominates over the gravity of the matter. There are especially autoironic passages, that indicate the epideictic character of this poetry. Ovid does not really want to be a teacher of either love or beauty, but he only wants to show his abilities as a poet writing a didactic poem just to give its readers some kind of intellectual enjoyment and delight, similar to that known from comedy. There is also one more epideictic aspect of Ovid’s poetry, who seems to create a new way of telling erotic. His main purpose is not to be bawdy or suggestive, but he tries to be above all gracefully refined.
Didacticism as a poetical form in Ovid’s 'Art of Love'
Keywords: Ovid; elegy; Roman elegy; Art of Love; didactic poetry; erotodidactic